Evaluation of carotid endarterectomy with sequential MR perfusion imaging: a preliminary report. - Gillard, J H; Hardingham, C R; Kirkpatrick, P J; Antoun, N M; Freer, C E; Griffiths, P D (American Journal of Neuroradiology, 1998)
BACKGROUND AND PURPOSE Current indications for carotid endarterectomy are determined by balancing the relative risks of surgery with the benefits of reduced risk of subsequent stroke. Our purpose was to use MR perfusion imaging to assess patients being considered for carotid endarterectomy and to monitor sequential changes in MR perfusion characteristics after surgery. In particular, we wished to determine whether this technique could be used to detect changes that might be related to post-carotid endarterectomy hyperemia.METHODS We used a single-section gradient-recalled echo sequence to investigate 14 patients being examined before possible surgery for carotid artery disease. In the 12 patients in whom carotid endarterectomy was performed, sequential studies were performed 3 to 5 days after surgery and at 3 months. Analysis of bolus-arrival-time (BAT) images was performed.RESULTS Significant delays in preoperative BAT images of 0.89 seconds (range, 0.05 to 3.22 seconds) were apparent between hemispheres. Excluding the two patients with contralateral internal carotid artery (ICA) occlusion, early arrival, possibly indicating postoperative hyperemia, was seen in five patients immediately after carotid endarterectomy but resolved within 3 to 5 months after surgery.CONCLUSION MR perfusion imaging shows differences in BAT between hemispheres in patients with ICA stenosis. Changes in perfusion characteristics after carotid endarterectomy are complex, and early BAT on the operative side can occur soon after endarterectomy in over half those patients without an occluded contralateral vessel. The significance of these findings with regard to patient outcome and risk of postoperative hyperemia requires further investigation.